Psychosocial interventions for informal caregivers of lung cancer patients: A systematic review. Issue 2 (24th November 2019) - Kedia, Satish K.; Collins, Andy; Dillon, Patrick J.; Akkus, Cem; Ward, Kenneth D.; Jackson, Bianca M.
Abstract: Objective: Caregivers of patients with lung cancer often face physical, emotional, and financial distress, which not only negatively affects the caregivers' mental health and quality of life but may also impact patients' well‐being. The purpose of this systematic review is to examine the content, delivery, and efficacy of psychosocial interventions targeting caregivers of lung cancer patients. Methods: Studies included in this systematic review assessed psychosocial interventions for caregivers of lung cancer patients that were published in English between January 2009 and December 2017. These interventions focused on burden, mental health, quality of life, self‐efficacy, and/or coping as outcome measures. CINAHL, PubMed, PsycInfo, Science Direct, and Web of Science databases were searched using the terms (lung cancer OR lung neoplasms OR thoracic cancer) AND (caregiver OR caregiving) AND (intervention OR program) to systematically review the relevant literature on this topic. Results: From the 22 studies included in this systematic review, interventions were classified into four categories: communication‐based interventions, coping skills training interventions, multicomponent interventions, and stress reduction interventions. The majority of the interventions (especially communication‐based and multicomponent) led to improvement, albeit not always statistically significant, in one or more outcomes; however, the most frequently reported improvements included, burden, distress, anxiety, depression, overall quality of life, self‐efficacy, and coping abilities. Conclusions: The unmet needs of informal caregivers of lung cancer patients have a significant impact on their mental health and quality of life, but this burden can be alleviated by psychosocial interventions that offer appropriate support, education, and resources.